Development of a colloidal gold immunochromatographic strip for the simultaneous detection of porcine epidemic diarrhea virus and transmissible gastroenteritis virus - Zhou, Jinzhu; Wu, Wei; Wang, Dandan; Wang, Wei; Chang, Xinjian; Li, Yunchuan; Li, Jizong; Fan, Baochao; Zhou, Junming; Guo, Rongli; Zhu, Xuejiao; Li, Bin (Frontiers in Microbiology, 2024)
In recent years, porcine diarrhea-associated viruses have caused significant economic losses globally. These viruses present similar clinical symptoms, such as watery diarrhea, dehydration, and vomiting. Co-infections with porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV) are common. For the rapid and on-site preliminary diagnosis on the pig farms, this study aimed to develop a colloidal gold immunochromatography assay (GICA) strip for the detection of PEDV and TGEV simultaneously. The GICA kit showed that there was no cross-reactivity with the other five common porcine viruses. With visual observation, the lower limits were approximately 104 TCID50/mL and 104 TCID50/mL for PEDV and TGEV, respectively. The GICA strip could be stored at 4°C or 25°C for 12 months without affecting its efficacy. To validate the GICA strip, 121 clinical samples were tested. The positive rates of PEDV and TGEV were 42.9 and 9.9%, respectively, and the co-infection rate of the two viruses was 5.8% based on the duplex GICA strip. Thus, the established GICA strip is a rapid, specific, and stable tool for on-site preliminary diagnosis of PEDV- and TGEV-associated diarrhea.